2017
DOI: 10.1063/1.5000373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H2 and D2 plasmas on the work function of caesiated materials

Abstract: Caesium-covered surfaces are used in negative hydrogen ion sources as a low work function converter for H–/D– surface production. The work function χ of the converter surface is one of the key parameters determining the performance of the ion source. Under idealized conditions, pure bulk Cs has 2.14 eV. However, residual gases at ion source background pressures of 10−7–10−6 mbar and the plasma surface interaction with the hydrogen discharge in front of the caesiated surface dynamically affect the actual surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Furthermore, the lowtemperature hydrogen plasma interacts with the converter surface, resulting in a redistribution of the Cs atoms. Additionally, this interaction can lead to a cleaning effect of the Cs layer performed by plasma particles, like neutral hydrogen atoms and hydrogen positive ions, probably together with the UV light emitted by de-excitation of neutral hydrogen, producing a decrease of the work function [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the lowtemperature hydrogen plasma interacts with the converter surface, resulting in a redistribution of the Cs atoms. Additionally, this interaction can lead to a cleaning effect of the Cs layer performed by plasma particles, like neutral hydrogen atoms and hydrogen positive ions, probably together with the UV light emitted by de-excitation of neutral hydrogen, producing a decrease of the work function [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the volume production of H − should not be influenced by the presence of Cs in the plasma and the additionally detected negative ions can be attributed to surface conversion at the caesiated V2A surface. Measurements of the work function under comparable plasma parameters at the laboratory experiment ACCesS have shown values down to 2.1 eV for caesiated surfaces [23][24][25]. Hence, it can be concluded that in this system formation of H − at a surface with 2.1 eV work function leads to an increase of the negative ion density by about a factor of 2.5 in maximum.…”
Section: Effect Of Caesiation At Homermentioning
confidence: 64%
“…Determination of the work function of different materials is performed at the laboratory setup ACCesS (planar ICP, ∅ = 15 cm, h = 10 cm, 600 W max.) [5,9,10]. Influence of plasma exposure on the WF is investigated by measuring the WF in short intermediate gas phases (around 3 min) alternating with long plasma exposure times (minutes up to hours).…”
Section: Experimental Setup and Materialsmentioning
confidence: 99%
“…However, in addition, Cs is the most reactive alkali metal and its high vapor pressure leads to a high volatility of the surface layer. Hence, under conditions of negative ion sources with non-negligible amounts of impurities from the background gases (vacuum of 10 −6 mbar) and interaction with the low pressure hydrogen plasma in front of the surface, high dynamics including deterioration [5] and redistribution [6] occur. The expected Cs consumption as well as a desired stable and homogenous work function thus drive the question for alternative materials to caesium [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation